Controversies and advances in the management of congenital ptosis - Mokhtarzadeh, Ali (Expert Rev Ophthalmol, 2015)
The management issues associated with pediatric ptosis begin with determining the etiology of the ptosis, and considering how the eyelid position affects the child’s visual and psychosocial development. These ultimately determine if and when surgical management should be undertaken. Surgical challenges include the lack of intraoperative feedback regarding the dynamic eyelid height and contour under general anesthesia. When the eyelid elevators do not function or if there is little drive to lift the involved eyelid, obtaining good surgical outcomes can be extremely challenging. A plethora of surgical techniques and materials have been developed, each with their own benefits and drawbacks. Careful preoperative evaluation, planning and counseling can usually result in satisfactory surgical results with happy parents and patients. Families should always be aware that the child will need to be followed long term for visual development, ocular health, and they need to be counseled regarding the possibility of revision surgery.